2006
DOI: 10.1007/s10750-006-0075-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of errors in sorting and identifying macroinvertebrate samples

Abstract: This study assesses the impact of errors in sorting and identifying macroinvertebrate samples collected and analysed using different protocols (e.g. STAR-AQEM, RIVPACS). The study is based on the auditing scheme implemented in the EU-funded project STAR and presents the first attempt at analysing the audit data. Data from 10 participating countries are analysed with regard to the impact of sorting and identification errors. These differences are measured in the form of gains and losses at each level of audit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 30 publications
2
28
0
1
Order By: Relevance
“…The same is true concerning precision and errors (Haase, Murray-Bligh, et al, 2006). On the other hand, all these studies clearly indicate that observed differences are not a weakness of the STAR/AQEM protocol but a general problem in sampling invertebrates in streams.…”
Section: Impact Of Modifications and Variability Of The Star/aqem Metsupporting
confidence: 54%
“…The same is true concerning precision and errors (Haase, Murray-Bligh, et al, 2006). On the other hand, all these studies clearly indicate that observed differences are not a weakness of the STAR/AQEM protocol but a general problem in sampling invertebrates in streams.…”
Section: Impact Of Modifications and Variability Of The Star/aqem Metsupporting
confidence: 54%
“…Taxa were identified to the level proposed by Haase et al (2006a), which ensured that taxa lists were comparable with regard to their taxonomic resolution. For most taxa, the resolution was at the genus or species level, but selected families such as Chironomidae, Naididae, or Tubificidae were determined only to the sub-family or family level.…”
Section: Sampling Designmentioning
confidence: 99%
“…found that subsampling of STAR-AQEM samples caused more than 50% of the overall replicate sampling variance for nearly half of all metrics analysed. In a companion study, Haase et al (2006) found significant effects of laboratory sampling sorting and taxonomic identification errors on the values of several macroinvertebrate metrics for the STAR-AQEM and RIVPACS methods.…”
Section: Comparison Of Precision Of Metricsmentioning
confidence: 92%